Changes In Indonesian Phonology In The Medan Dialect: Generative Analysis - Khairiah Zahra; Zahira Shofa Sihotang; Yani Lubis (Universitas Palangka Raya, 2023)
Indonesian is one of the many dialects of Malay. Therefore, High Malay (Melaka/Riau) is used as the basic language of Indonesia. Even though more than 90% of Indonesians are able to understand and speak the language, most Indonesians do not regard their mother tongue as Indonesian. The most common